Herbal and traditional Herbal Medicinal Products, EU Herbal monographs and EU list - Petrović Silvana (Pharmaceutical Association of Serbia, Belgrade, Serbia, 2019)
According to legislation of EU, as well as of our country, herbal medicinal products (HMPs) and traditional herbal medicinal products (THMPs) are categories of medicinal products. As active ingredients, they contain herbal drugs (herbal substances) and/or herbal drug preparations (herbal preparations). HMPs are authorized based on proved quality, clinical efficacy and safety. THMPs are registered based on proved quality and sufficient data on traditional use (acceptable safety level and plausible efficacy). The Committee on Herbal Medicinal Products (HMPC) of the European Medicines Agency (EMA) publishes EU herbal monographs, which comprise preclinical and clinical data on HMPs with well-established use (WEU), as well as data on traditional use (TU) for THMPs. HMPC also develops drafts of EU list entries for THMPs, which are adopted and their final versions are published by the European Commission. By the end of July 2019, HMPC issued 160 final monographs, which are available on the EMA website (157 monographs for 156 herbal drugs and herbal drug preparations, two monographs for two herbal drug combinations, and monograph for herbal tea combinations); EU list entries on 13 herbal drugs and preparations were finalized. This paper provides an overview of the therapeutic areas and indications approved in these final EU monographs. In addition, overview of HMPs and THMPs, which are authorized/registered in the Republic of Serbia is given.